Benign cutaneous polyarteritis nodosa in children below 10 years of age--a clinical experience. Issue 2 (February 1995) - Kumar, L; Thapa, B R; Sarkar, B; Walia, B N
Abstract : OBJECTIVE--To report 10 children younger than 10 years of age with benign cutaneous polyarteritis nodosa (BCPAN). METHODS--Ten children aged 1.25-10 years (mean 4.7 years; M:F = 7:3) were admitted with an unusual vasculitis. The clinical features, laboratory investigations, treatment and follow up data were analysed. RESULTS--Clinical features of these patients included: fever (10), peripheral gangrene (eight), livido reticularis (four), ulceration, nodules and vesiculobullous lesions alone or in combination (10), black necrotic patches over limbs and trunk (three), and arthralgia or swelling of large joints (seven). Cryoglobulinaemia was transient in three children, lasting for eight months in one of them. Histopathology of the skin lesions revealed vasculitis of small and occasionally medium sized blood vessels in nine of the 10 children. Possible association of BCPAN was noted with diphtheria-pertussistetanus immunisation (one), drugs (two), streptococcal infection (two), wasp sting (one), and falciparum malaria (one). The clinical course was interspersed with remissions and exacerbations. Response to corticosteroids alone occurred in seven patients, while three children needed cytotoxic drugs in addition. In a follow up of 5.6 years (mean) no evidence of systemic involvement was noted. CONCLUSIONS--A rare form of vasculitis, BCPAN, is reported in children. The features that distinguished our patients from those reported earlier were onset in the first decade of life and higher incidence of peripheral gangrene.